Скіфські кулеподібні бронзові наконечники стріл - Могилов, О.Д. (Археологія, 2018)
Стаття присвячена характеристиці бронзових кулеподібних наконечників стріл, розповсюджених у Причорномор’ї в ранньоскіфський час. The bronze bullet arrowhead accompanied by materials of an early Scythian time during the research of the internal rampart of the Motronyn hillfort in a Tiasmyn River basin, in 2017 was found. It complemented a small series of the similar items that originate from the Black Sea region. Approximately thirty similar finds are known today. The nearest analogies were found on the settlements of Zhabotyn and Ivanivka, on the South of Dnieper River Right-bank Forest-steppe, in the Tiasmyn River basin. A similar object occured near the Lykhachivka village in Povorsklia. Such types of arrowhead series are known from the territory of the Northern Caucasus: from the Zheleznodorozhny and Komarovsky burial grounds, from the Krasnoe Znamya, Mineralnye Wody and Bazhigan archaeological sites. They were found in Pre-Kelermes quiver set in a burial at Amasya in Turkey, and probably mark the Scythian campaigns to Anterior Asia. Analogies are known at the Sauromats of the Volga and the Urals, the Saks of Central Asia, the tribes of the Scythian time of Northern Kazakhstan and Tuva. The arrowheads from the Black Sea region are dated by the early Scythian time (7th — the first half of the 6th century BCE). Most of them are known in the archaeological sites of the Kelermes stage from the Komarovsky, Zheleznodorozhny, Mineralovodsky burial grounds. The burial near Amasya specifies on their existence on the Pre-Kelermes stage. The bullet arrowheads had a less area of contact with the target surface and could have a larger penetration. They could be used for fights against warriors dressed in defensive armour. As such finds are widespread on the vast spaces of Eurasia, it is possible to suppose the independent origin of similar artefacts in different regions. Probably, the bone arrowheads of a similar shape served as the prototypes, and the process of transformation passed within the framework of the replacement process of bone to a bronze and iron ones, well-known in the Early Iron Age. В 2017 г., во время исследования внутреннего вала Мотронинского городища бассейна р. Тясмин, был найден бронзовый пулевидный наконечник стрелы, сопровождавшийся материалами раннескифского времени. Он дополнил небольшую серию подобных вещей, происходящих из Причерноморья. Сегодня известно немногим более 30 похожих изделий. Ближайшие аналогии известны из сел Жаботина и Ивановки, на юге Днепровской Правобережной Лесостепи, в бассейне р. Тясмин. Подобный предмет найден у Лихачевки в Поворсклье. Целая серия таких изделий происходит с Северного Кавказа: Железнодорожный и Комаровский могильники, Красное Знамя, Минеральные Воды, Бажиган. Найдены они в погребении у Амасьи в Турции. Здесь они были в докелермесском колчанном наборе, и вероятно, маркируют скифские походы в Переднюю Азию. Аналогии известны у савроматов Поволжья и Приуралья, саков Средней Азии, племен скифского времени Северного Казахстана и Тувы. Стрелы из Причерноморья датируются раннескифским временем (VII — первая половина VI вв. до н. э.). Большинство из них известно в памятниках келермесского этапа: захоронения Комаровского, Железнодорожного, Минераловодского могильников. Захоронение близ Амасьи указывает на их бытование и на докелермесском этапе. Пулевидные стрелы имели меньшую площадь контакта с поражаемой поверхностью и могли иметь большую пробиваемость. Они могли использоваться для борьбы с одетыми в защитные доспехи воинами. Поскольку их находки распространены на огромных просторах Евразии, можно предполагать независимое возникновение подобных артефактов в разных регионах. Вероятно, прототипами послужили костяные стрелы аналогичной формы, а сам процесс трансформации проходил в рамках процесса замены кости бронзой и железом, известного в раннем железном веке.